Ghrelin and its interactions with growth hormone, leptin and orexins: implications for the sleep-wake cycle and metabolism - García García, Fabio (2014)
Several studies have shown that ghrelin administration promotes wakefulness in rodents, while in human males it induces sleep but has no effect in women. Ghrelin also plays an important role in metabolism and appetite regulation, and as described in this review may participate in the energy balance during sleep. In this review, we summarize some of the effects induced by ghrelin administration on the sleep–wake cycle in relation to the effects of other hormones, such as growth hormone, leptin, and orexin. Finally we discuss the relationship between sleep deprivation, obesity and ghrelin secretion pattern.